Gambaran Regulasi Emosi Remaja Sekolah Menengah Pertama di SMP Sultan Agung 4 Semarang - Sesilia Apriliani; Indra Tri Astuti; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Emotional regulation is the ability of individuals to recognize, manage, and control their emotions, which is crucial for adolescents, especially when facing various situations in the school environment. This study motivated by the high incidence of stress and emotional problems among students, which can impact their academic performance and social relationships. Method: This research employs a quantitative approach using a survey method. Questionnaires were distributed to 173 students from grades 7, 8, and 9 at SMP 4 Sultan Agung. The obtain data were analyzed to identify the depiction of students emotional regulation and the factors influencing it. Result: Based on the analysis results, from 193 respondents, it showed that 81 respondents (46.8%) had good emotional regulation, while 92 respondents (53.2%) had sufficient emotional regulation. There was a significant difference in emotional regulation ability based on grade level, where students in higher grades had better emotional control. Internal and external factors can affect students' emotional regulation. Conclusion: This study concludes that the emotional regulation of students at SMP 4 Sultan Agung varies, and it is essential for schools and parents to collaborate in creating an environment that supports the development of students' emotional regulation skills.